Causes for the Change Orders in Road Construction: Reviewed from Owner - Mega Waty; Hendrik Sulistio (Communications - Scientific letters of the University of Zilina, 2022)
Changes in road construction are affected by the owner and contractor at the beginning, middle, or end of the project. This study aims to determine the ranking of the factors that cause change orders for road construction from the owner’s point of view. Data was collected by distributing questionnaires and interviews to project owners. Reliability and validity tests involving 32 respondents resulted in 48 causes of change orders. This study quantifies the relative importance of the factors that cause change orders and shows the ranking of factors and groups that cause change orders according to their level of importance for causes of change orders. This goal is achieved through the analysis of the results of the interviews. According to the calculation of the Relative Importance Index (RII), all the factors and groups are ranked and the most significant ranking is determined regarding the causes of the change orders. Keywords: cause of change order, owner, road project